Expression of CIP2A and CD44v6 in condyloma acuminatum-involved skin and its correlation with patients' prognosis - ZHANG Yijie; YANG Can; LIN Yongli (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the expression levels of cancerous inhibitor of protein phosphatase 2A (CIP2A) and CD44v6 in condyloma acuminatum (CA)-involved skin and to analyze the correlation between their expression and the distribution of HPV genotypes in CA patients and their prognosis. Methods The study group included 100 cases of CA patients who were admitted to our hospital from April 2020 to April 2023. The patients were divided into the good prognosis group and poor prognosis group according to their prognosis. The CA-involved skin samples were collected during the operation. The control samples were obtained from 100 subjects who underwent vulvoplasty or circumcision during that time in our hospital. Real-time fluorescence quantitative PCR was used to detect the expression levels of CIP2A and CD44v6 mRNA in the tissue specimens. The expression levels of CIP2A and CD44v6 mRNA were compared between the study and the control groups, different HPV typing groups, and good prognosis and poor prognosis groups. The relationship between the expression of CIP2A and CD44v6 in the CA tissues and the clinical features was analyzed, while multifactorial COX regression was used to analyze the influencing factors on the prognosis of CA patients. ROC curves were plotted to analyze the influence of CIP2A and CD44v6 on the predictive value of poor prognosis in CA patients. Results The expression levels of CIP2A and CD44v6 mRNA in the study group were significantly higher than that in the controls (CIP2A: 2.19±0.40 vs 1.01±0.24, t=25.24, P<0.05; CD44v6: 1.75±0.33 vs 1.02 ±0.22, t=18.41, P<0.05). The expression levels of CIP2A and CD44v6 mRNA were in an ascending order of the low-risk, high-risk and mixed groups (all P<0.05). The expression levels of CIP2A and CD44v6 mRNA in the poor prognosis group were significantly higher than that in the good prognosis group (CIP2A: 3.58±0.62 vs 1.62±0.31, t=21.05, P<0.05; CD44v6: 2.57±0.49 vs 1.42±0.26, t=15.26, P<0.05). The CIP2A and CD44v6 expression correlated with wart number and its diameter (both P<0.05). Multifactorial COX regression analysis showed that the expression of CIP2A and CD44v6, as well as the number and diameter of warts, were risk factors for the poor prognosis of CA patients (P<0.05). The ROC curves showed that the AUC for predicting a poor prognosis of CA patients was 0.866 for CIP2A, 0.860 for CD44v6, and 0.928 for the combination of both. The latter was superior to the respective individual predictions (Zcombination vs CIP2A=2.72, Zcombination vs CD44v6=2.73, both P<0.05). Conclusions The expression levels of CIP2A and CD44v6 are significantly elevated in CA-involved skin. Expression levels of both CIP2A and CD44v6 are associated with the distribution of HPV genotypes and their prognosis. The combination of CIP2A and CD44v6 values can improve the prediction of the prognosis of CA patients.